The life and operas of Verdi - Greenberg, Robert, 1954-; Teaching Company (Springfield, VA : Teaching Co., 2003)
Describes the life and operas of the 19th century Italian composer, Giuseppe Verdi. Provides analysis and interpretation.
lecture 1. La bell'Italia -- lecture 2. Beginnings -- lecture 3. Oberto -- lecture 4. Nabucco -- lecture 5. Nabucco, conclusion and risorgimento -- lecture 6. I Lombardi -- lecture 7. I Lombardo, conclusion, and Ernani -- lecture 8. Macbeth -- lecture 9. I masnadieri -- lecture 10. Luisa Miller and Rigoletto -- lectures 11. Rigoletto, Act I continued -- lecture 12. Rigoletto, Acts I, II and III -- lecture 13. Rigoletto. Act III continued -- lecture 14. Rigoletto, conclusion and Il trovatore -- lecture 15. Il trovatore, conclusion and La traviata -- lecture 16. Un ballo in maschero -- lecture 17. Un ballo in maschera, conclusion -- lecture 18. La forza del destino -- lecture 19. Don Carlo -- lecture 20. Don Carlo, conclusion -- lecture 21. Aida -- lecture 22. Aida, conclusion -- lecture 23. The requiem -- lecture 24. The requiem, conclusion -- lecture 25. Otello -- lecture 26. Otello, conclusion, Falstaff -- lecture 27. Falstaff, Act I, Sc. 1 -- lecture 28. Falstaff, Act I, Sc. 1, conclusion, Sc. 2 -- lecture 29. Falstaff, Act I, Sc. 2, conclusion, Act II, Sc. 1 -- lecture 30. Falstaff, Act II, Sc. 1, conclusion, Sc. 2 -- lecture 31. Falstaff, Act II, Sc. 2 continued -- lecture 32. Falstaff, Act II, conclusion, Act III.
In 4 containers.
"San Francisco performances"--Container.
32 lectures.
Lecturer: Robert Greenberg.
DVD, region 1.
Keywords: Verdi, Giuseppe, -- 1813-1901 -- Criticism and interpretation; Verdi, Giuseppe, -- 1813-1901.; Composers -- Italy -- Biography; Operas -- Analysis, appreciation